Sarny, a life remembered - Paulsen, Gary (New York, N.Y. : Bantam Doubleday Dell Books for Young Readers, 1999)
Continues the adventures of Sarny, the slave girl Nightjohn taught to read, through the aftermath of the Civil War during which time she taught other Blacks and lived a full life until age ninety-four. In this companion novel to the acclaimed "Nightjohn, " Sammy, the young slave girl who learned to read in "Nightjohn, " is now a young widow. She flees the plantation in the last days of the Civil War, a free woman in search of her sold-away children. Sarny's story gives a panoramic view of America in a time of tragedy, trial, and hoped-for change, until her last days in the 1930s
Originally published: New York : Delacorte Press, 1997
"Laurel-leaf books."
Sequel to: Nightjohn
4.3
Keywords: Slavery -- Fiction; African Americans -- Fiction; Teaching -- Fiction; Fiction